Genetic differentiation among populations of the threatened Bellevalia webbiana (Asparagaceae) and its consequence on conservation. (6th December 2020) - Peruzzi, Lorenzo; Astuti, Giovanni; Algisi, Sabrina; Coppi, Andrea
Abstract: The narrow central Italian endemic and threatened Webb's hyacinth ( Bellevalia webbiana ), a perennial herb, is a clear example of a species that has disappeared from several localities due to the development of human settlements. We characterized population genetics of this species to infer possible threats to its viability. We used a dominant DNA fingerprinting approach to infer genetic relationships among the five richest populations known for this species (each with N > 50 individuals). We highlighted phenomena of genetic erosion, with values of intrapopulation-gene-diversity quite similar across all populations (mean value 0.113), but a mean F st value only slightly below the mean found in other plant species using similar approaches. Despite an overall genetic similarity among populations, a population from Faenza (Emilia-Romagna) is clearly separated from all the others on genetic grounds, and may be defined as an Evolutionarily Significant Unit, worth of special conservation attention. Interestingly, this latter population is also behaving differently from all the others in terms of both vegetative and reproductive functional strategies. Our results highlight the relevance of evolutionary approaches to conservation biology for preserving a genetic diversity linked to local adaptations.